Optimization of organic waste in TPS 3R Enggal Nyaman for grape cultivation - Eko Muh Widodo; Muhammad Al Anwar; Muhammad Arif Rokhman; Muhammad Ardiansyah; Wahyu Sangaji; Feriando Andromeda (Universitas Muhammadiyah Magelang, 2022)
One of Muntilan's TPS is the TPS 3R Enggal Nyaman in Ngemplak Hamlet. This TPS was constructed in 2014 and is equipped with sufficient and ready-to-use equipment. TPS 3R has a green house that is currently only used for ornamental plant planting. As a result, grape cultivation is being developed to increase the added value of organic products produced. Training and mentoring are used to provide this program. As a result of this program, partners able to make liquid fertilizer on their own and use it as a grape cultivation supporter in the new green house. TPS 3R Enggal Comfortable will benefit economically from this cultivation in the long term.